Eating behavior features and preferred diets in underweight and obese young men - N. I. Mikhaylova; B. B. Pinkhasov; M. Yu. Sorokin; V. G. Selyatitskaya (Ожирение и метаболизм, 2023)
BACKGROUND: Actual nutrition and eating behavior features affect the formation of excess or underweight which in turn are risk factors for the development of chronic non-infectious diseases.AIM: To assess eating behavior features and consumption of basic nutrients in relation to metabolic disorders in underweight and obese young men of military age.MATERIALS AND METHODS: The study enrolled 86 young men aged 18 to 23 years that were referred by military enlistment office due to violations in body weight and examined in the hospital. Participants were divided into 2 groups depending on the value of the body mass index (BMI): group 1 (n=41) — underweight (Uw) young men; group 2 (n=45) — obese (Ob) young men. Anthropometric, hormonal and biochemical parameters of the body were measured; the type of eating disorder (ED) was evaluated using the Dutch DEBQ questionnaire, the presence and severity of anxiety and depressive disorders were assessed using the Hospital Anxiety and Depression Scale; assessment of the actual diet was performed using «Somatonic» computer soft.RESULTS: Absolute intake of all essential nutrients was higher in Ob young men; the relative consumption of protein and cholesterol was higher in Uw young men, whereas relative fats intake was higher in Ob group. EDs were statistically significantly more common in Ob young men. The values of all anthropometric indicators were higher in Ob group, while Uw young men predominantly demonstrated deficiency of the body fat component which did not affect key hormonal and metabolic indicators values. In Ob young men carbohydrate metabolism hormonal regulation disorders along with increased blood pressure were revealed.CONCLUSION: The ratio of proteins and fats intake should be taken into account in dietary regimens composition; Uw young men need to increase the proportion of fat and reduce protein intake, whereas Ob young men on the contrary need to reduce the proportion of fat and increase amount of proteins enhancing energy expenditure due to the specific dynamic food action.